2012
DOI: 10.1021/jf303471f
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Antihypertensive and Antihyperlipidemic Effects of Bamboo Shoot Angiotensin Converting Enzyme Inhibitory Peptide in Vivo

Abstract: Cardiovascular protective functions of bamboo shoot angiotensin converting enzyme (ACE) inhibitory peptide (BSP) from bamboo shoot were evaluated, including antihypertensive effect on spontaneously hypertensive rats (SHRs) and antihyperlipidemic effect on high-fat-diet-induced rats. Thirty-day antihypertensive effects of BSP on SHRs were assayed. Asp-Tyr [10 mg/day kg body weight (BW)] and BSP (50 mg/day kg BW) significantly reduced ACE activity in lung at the same level (p < 0.05), while BSP (50 mg/day kg BW)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 48 publications
1
20
1
Order By: Relevance
“…At present, studies of the chemical constituents of bamboo revealed the occurrence of molecules such as flavonoids, lignans, and polyphenols [3 -6]. In our recent phytochemical investigations, two new compounds, xylitol 1-O-(6 0 -O-p-hydroxylbenzoyl)-glucopyranoside (1) and bambulignan B (2) (Figure 1), together with three known ones (3)(4)(5), were obtained from this plant. Compound 1 bears a rare xylitol group, and compound 2 is a new member of bamboo lignans ( Figure 1).…”
Section: Introductionmentioning
confidence: 93%
“…At present, studies of the chemical constituents of bamboo revealed the occurrence of molecules such as flavonoids, lignans, and polyphenols [3 -6]. In our recent phytochemical investigations, two new compounds, xylitol 1-O-(6 0 -O-p-hydroxylbenzoyl)-glucopyranoside (1) and bambulignan B (2) (Figure 1), together with three known ones (3)(4)(5), were obtained from this plant. Compound 1 bears a rare xylitol group, and compound 2 is a new member of bamboo lignans ( Figure 1).…”
Section: Introductionmentioning
confidence: 93%
“…To overcome these limitations, an increasing number of interest has been paid to find new ACE inhibitors that are capable of providing similar therapeutic effects, but with greater safety margins. Edible plants targeting ACE inhibition, such as peptides, flavonoids, and triterpenes, have been reported in the literature [39][40][41].…”
Section: β-Sitosterol Glucoside (9)mentioning
confidence: 99%
“…1B. Because p-CA has been reported as a major phenolic compound contained in many bamboo species such as Phyllostachys pubescens (Pradelle) Mazel ex J. Houz [30] and Sasa quelpaertensis Nakai [31], we analyzed the content of p-CA in BCTE using HPLC and it was determined to be 1.7%. ) in the absence and presence of BCTE (10, 30, or 100 µg/mL) or p-CA (10 µg/mL), followed by incubation for 24 h. The whole cell lysates were subjected to western blot analysis for procaspase 3 and its cleaved form (A), and Bax and Bcl-2(B).…”
Section: Resultsmentioning
confidence: 99%
“…4). Like the cases of other bamboo species [30,31], p-CA was assumed to contribute to bioactivities of BCTE. The protective effects of p-CA against the UV-induced inflammatory responses or injury has been previously observed in cells and in vivo models [32][33][34].…”
Section: Discussionmentioning
confidence: 99%